A Focus on the Epidemiology of Uveitis. (2nd January 2018) - Tsirouki, Theodora; Dastiridou, Anna; Symeonidis, Chrysanthos; Tounakaki, Ourania; Brazitikou, Irini; Kalogeropoulos, Christos; Androudi, Sofia
ABSTRACT: Purpose : Uveitis is a common, sight-threatening inflammatory ocular disease and includes multiple heterogeneous clinical entities. The prevalence of various types of uveitis depends upon multiple factors, such as age, sex, race, geographic distribution, environmental influence, genetics, and social habits. Epidemiologic research of uveitis is necessary to understand the etiology and immunopathogenesis of this group of diseases. The present study attempts to concentrate on the most recent information on the epidemiology of uveitis and compare it with previous knowledge. Methods : An extensive literature search was performed in the Medline database (PubMed) and included surveys completed until 2015. Articles that reported prevalence and incidence were studied. References cited in the articles were also studied. Results : The incidence and prevalence of uveitis differs based on age, anatomic location of the inflammatory process (anterior, intermediate, posterior uveitis, panuveitis), gender, histopathology (granulomatous, non-granulomatous), type of inflammatory process (acute, chronic, recurrent), and etiology (infectious, non-infectious). Prevalence differs by geographic location. Idiopathic anterior uveitis is the most common form of uveitis in the community. Infectious causes are common (30–60%) in the developing countries. Herpes and toxoplasmosis are the leading infectious causes of uveitis. Non-infectious uveitic conditions are generally more common in the developed world. An increase in the prevalence of infectious etiologies, including tuberculosis and syphilis, has been seen in developed countries. Introduction of new treatment options has also changed patterns of disease. Conclusions : Introduction of new uveitis entities, changes in the incidence of already known disease and increased availability of diagnostic testing have all altered the epidemiology of uveitis in recent years. Knowledge of regional patterns of disease is essential. A more detailed classification of uveitis with the establishment of uniform diagnostic criteria and prospective population based studies would certainly benefit epidemiologic research and clinical practice.